The Role of SIRT3 in the Brain Under Physiological and Pathological Conditions - Sidorova-Darmos, Elena; Sommer, Rosa; Eubanks, James H. (Frontiers in Cellular Neuroscience, 2018)
Sirtuin enzymes are a family of highly 7 conserved protein deacetylases, namely SIRT1 through SIRT7, whose enzymatic activities require the cofactor nicotinamide adenine dinucleotide (NAD+). Sirtuins reside in different compartments within cells, and their activities have been shown to regulate a number of cellular pathways involved in but not limited to stress management, apoptosis and inflammatory responses. Given the importance of mitochondrial functional state in neurodegenerative conditions, the mitochondrial SIRT3 sirtuin, which is the primary deacetylase within mitochondria, has garnered considerable recent attention. It is now clear that SIRT3 plays a major role in regulating a host of mitochondrial molecular cascades that can contribute to both normal and pathophysiological processes. However, most of the currently available knowledge on SIRT3 stems from studies in non-neuronal cells, and the consequences of the interactions between SIRT3 and its targets in the CNS are only beginning to be elucidated. In this review, we will summarize current advances relating to SIRT3, and explore how its known functions could influence brain physiology.